2k-5=-13

Simple and best practice solution for 2k-5=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k-5=-13 equation:


Simplifying
2k + -5 = -13

Reorder the terms:
-5 + 2k = -13

Solving
-5 + 2k = -13

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 2k = -13 + 5

Combine like terms: -5 + 5 = 0
0 + 2k = -13 + 5
2k = -13 + 5

Combine like terms: -13 + 5 = -8
2k = -8

Divide each side by '2'.
k = -4

Simplifying
k = -4

See similar equations:

| 4n-3=n+9 | | 3x^2-19x^2-14x=0 | | 60=(6-9x) | | x+x+20=72 | | 3x+3=5y | | -9+-11+-18+-19+-21+-20+-15= | | 4x+-7-6x=5-4x+4 | | 60=(9x-3) | | x+20=72 | | x/9=82 | | 9/x=82 | | 4x-2=1x | | 0.8y-11=1.6y-15 | | 4(2+3x)= | | x/-3.2-19 | | x+20x=72 | | p^2=-6 | | 3-(12-m)=-1(m-8) | | 7(3c+1)=5c-2(c+3) | | 15=-3(a+2)+3a | | y=7.50+2.50 | | 2n(1)=1.30 | | 3-x+11=10 | | 3x(6)=3.90 | | 2(3x-1)+5y=53 | | 6-y=0 | | 4(17.3)= | | 8(2-p)=24 | | 3+2i=0 | | -3x-(3x)=-24 | | 10x^2+3=-143 | | 12-36x= |

Equations solver categories